Using research in the teaching of management - C. Orpen (South African Journal of Business Management, 1986)
It is argued (i) that there is considerable scope for using research in teaching management, and (ii) that this does not require that the teacher be an active and expert researcher. A number of different ways of using research in teaching are discussed and suggestions provided for using them most effectively.
Keywords: 650